The Current Research Trend about Machine Learning as a New Way of Fostering Islamic Education in School - Bahrul Ulum; Nanang Qosim (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
This study has the purpose of observing the usage of machine learning as a new way of teaching Islamic education according to the Qur'an and hadith to the young generation. The method used for data collection is bibliometrics, using secondary data in the form of metadata on the Scopus website. The sample is divided into two charts: the Qur'an and the hadith. Around 49 samples were found for the Qur'an category and 16 for the Hadith category. The data was analyzed using bibliometric methods with two software. The result of this study was that the most used words in the author's keywords for Qur'an subjects were machine learning SVM, KNN, and ANN. This means that SVM, KNN, and ANN were used for certain purposes and situations in analyzing the interpretation result inside the text of the Qur'an done by Ulamas. The practical implication of this study is to be used as a reference for Islamic education in Indonesia to use machine learning features.Â